TECHNICAL REGULATION AS THE LEGAL REGULATION IN THE SPHERE OF ENTREPRENEURAL ACTIVITY - A. Panova (Russian Journal of Economics and Law, 2009)
The article views the topical problems of technical regulation of entrepreneurial relationships. The institution of technical regulation is investigated, the balance of legal regulation and technical regulation categories is shown. The author states that technical regulation is a legal form of the state regulation of entrepreneurial activity. Special attention is paid for the objectives, principles and peculiar features of technical regulation, as well as the mechanism of technical regulation of relationships in the sphere of entrepreneurial activity.